Moving From Theory To Practice: Creating Empirical, Digital Game-Based Research With K-12 Teachers - Jenson, Jennifer; Herbert, Cristyne (AoIR Selected Papers of Internet Research, 2017)
Acknowledging the persuasiveness of general arguments for serious uses of ‘serious games’, this research project addresses a need for a deeper understanding of how teachers can be practically supported in the use of digital games in the classroom, focusing specifically on developing teaching strategies by way of professional development, and guided support. In this paper, we outline the particular pedagogical strategies found most effective for game-play in K-12 classrooms, what we label meaningful, structured, and supported digital game-play.